Increasing transports of volume, heat, and salt towards the Arctic in the Faroe Current 1993–2013 - B. Hansen; K. M. H. Larsen; H. Hátún; R. Kristiansen; E. Mortensen; S. Østerhus (Zenodo, 2015)
The flow of warm and saline water from the Atlantic Ocean, across the Greenland– Scotland Ridge, into the Nordic Seas – the Atlantic inflow – is split into three separate branches. The most intensive of these branches is the inflow between Iceland and the Faroe Islands (Faroes), which is focused into the Faroe Current, north of the Faroes. The Atlantic inflow is an integral part of the North Atlantic thermohaline circulation (THC), which is projected to weaken during the 21 century and might conceivably reduce the oceanic heat and salt transports towards the Arctic. Since the mid-1990s, hydrographic properties and current velocities of the Faroe Current have been monitoredalong a section extending north from the Faroe shelf. From these in situ observations, time series of volume, heat, and salt transport have previously been reported, but the high variability of the transport series has made it dicult to identify trends. Here, we present results from a new analysis of the Faroe Current where the in situ observations have been combined with satellite altimetry. For the period 1993 to 2013, we findnbsp;the average volume transport of Atlantic water in the Faroe Current to be 3.80.5 Sv (1 Sv= 106 m3 s????1) with a heat transport relative to 0 C of 12415TW (1TW= 1012 W). Consistent with other results for the Northeast Atlantic component of the THC, we find no indication of weakening. The transports of the Faroe Current, on the contrary, increased. The overall trend over the two decades of observation was 98% for volume transport and 189% for heat transport (95% confidence intervals). During the same period, the salt transport relative to the salinity of the deep Faroe Bank Channel overflow (34.93) more than doubled, potentially strengthening the feedback on thermohaline intensity. The increased heat and salt transports are partly caused by the increased volume transport and partly by increased temperatures and salinities of thenbsp;Atlantic inflow, attributed mainly to the weakened subpolar gyre./p>